Avaliação dos parâmetros físico-químicos e zootécnicos no cultivo do camarão marinho Litopenaeus vannamei em viveiros tipo estufa - Medeiros, Silvestre Braga de (Universidade Federal Rural do Semi-Árido, 2019)
During the experimental period the physico-chemical and zootechnical parameters of the Litopenaeus vannamei shrimp were evaluated in three different treatments based on different storage densities: 105 in nursery 1 or V1, 70 in nursery 2 or V2 and 111 prawns.m-2 in nursery 3 or V2, in a maximum cultivation period of 43 days. The physico-chemical variables evaluated were temperature, dissolved oxygen (OD), salinity, hydrogen ionic potential (pH), ammonia, nitrite and nitrate, among which only nitrite presented a significant difference between treatments in a short period of time. Survival in V1 was reduced in relation to the other treatments. Probably this was due to structural problems of the greenhouses, followed by rainfall precipitation that led to variations in temperature and salinity, thus directly influencing the production / productivity and the Apparent Food Conversion Factor (FCAA). It was not possible to observe a good compensatory effect on the growth of the animals in the treatments, a fact probably due to low salinity. The V2 treatment obtained better gains in weight, final weight, yield and productivity in relation to the other treatments, probably due to its low density. In this way, the results in V2 were more satisfactory.
Monografia
Keywords: Camarão; Densidade; Estufa; Salinidade; Densities; Greenhouse; Salinity; Shrimp; CIENCIAS AGRARIAS::RECURSOS PESQUEIROS E ENGENHARIA DE PESCA